2020
DOI: 10.3892/or.2020.7865
|View full text |Cite
|
Sign up to set email alerts
|

Utility of flow cytometry and gene rearrangement analysis in tissue and blood of patients with suspected cutaneous T‑cell lymphoma

Abstract: Cutaneous T-cell lymphoma (CTCL) is difficult to diagnose at an early stage. Current diagnostic tools include clinical examination, histomorphologic analysis, immunohistochemistry, flow cytometry of peripheral blood and/or lesional tissue, and evaluation of T-cell receptor (TCR) clonality by gene rearrangement analysis (TCRGR). Advances in genomic sequencing, including high-throughput sequencing (HTS), can be used to identify specific clones of rearranged TCR genes. Even with all of these tools, CTCL can take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…However, there may be few malignant cells in early-stage MF with little sign of clonality, rendering PCR testing unreliable in a significant fraction of early cases [41,44]. High-throughput, next-generation TCR skin biopsy gene sequencing or peripheral blood samples is an emerging technique with potentially higher specificity than PCR-based techniques for differentiating MF from BIDs [44][45][46].…”
Section: Physical and Histopathological Examinationmentioning
confidence: 99%
“…However, there may be few malignant cells in early-stage MF with little sign of clonality, rendering PCR testing unreliable in a significant fraction of early cases [41,44]. High-throughput, next-generation TCR skin biopsy gene sequencing or peripheral blood samples is an emerging technique with potentially higher specificity than PCR-based techniques for differentiating MF from BIDs [44][45][46].…”
Section: Physical and Histopathological Examinationmentioning
confidence: 99%
“…4 In addition, FC may not accurately pick up T-cell clones and T-cell rearrangement studies are often needed for diagnosis of T-cell lymphoma, though this is typically managed by the pathologist and not the ordering provider. 82…”
Section: Biopsymentioning
confidence: 99%
“…Providers should monitor all patients with negative biopsy results for persistent signs and symptoms of lymphoma and pursue larger‐volume biopsy if clinical suspicion for lymphoma remains high 4 . In addition, FC may not accurately pick up T‐cell clones and T‐cell rearrangement studies are often needed for diagnosis of T‐cell lymphoma, though this is typically managed by the pathologist and not the ordering provider 82 …”
Section: Introductionmentioning
confidence: 99%
“…42 Recent studies have suggested that next generation sequencing (NGS) may be more sensitive and/or specific for assessing T-cell clonality in MF/SS, but NGS is not yet widely available. [43][44][45] The extent to which MF/SS may be preceded by a pre-malignant state, analogous to monoclonal B-cell lymphocytosis (MBL) or monoclonal gammopathy of undetermined significance (MGUS), is debatable and poorly defined. 46 The malignant lymphocytes in MF/SS are usually CD3 + CD4 + and CD8 À , but frequently lose the expression of other pan-T-cell antigens.…”
Section: Mycosis Fungoidesmentioning
confidence: 99%
“…Moreover, some MF cases may not have a detectable T‐cell clone 42 . Recent studies have suggested that next generation sequencing (NGS) may be more sensitive and/or specific for assessing T‐cell clonality in MF/SS, but NGS is not yet widely available 43–45 . The extent to which MF/SS may be preceded by a pre‐malignant state, analogous to monoclonal B‐cell lymphocytosis (MBL) or monoclonal gammopathy of undetermined significance (MGUS), is debatable and poorly defined 46 .…”
Section: Diagnosismentioning
confidence: 99%